Membaca Hari-Hari Terakhir Seorang Seniman dan Arus dalam Pendekatan Etnosemantik Goodenough (Malay Literature, 2022)
This article discusses the position of the novels Hari-hari Terakhir Seorang Seniman (1979) and Arus (1985) by Anwar Ridhwan as these are considered to be cultural products and behaviors of the Malay community. Based on the interpretation of the novels, from an ethnosemantics study by Goodenough proves that cultural products (literature) are the collective knowledge system of the Malay society in the 1940s and 1970s. In these two novels, Anwar Ridhwan has created a discourse of knowledge and cultural phenomena to discuss various issues in his society. It includes three main elements which are conflict of values, psychosocial and social leadership which can be connected with knowledge system, philosophy, public thinking and cultural behavior collectively. These works can be understood through content analysis to understand the forms of thought, cultural patterns, and behavior that form the basis of a society’s knowledge system which is the focus of Anwar Ridhwan’s novels. Therefore, these two novels in Goodenough’s ethnosemantics perspective are social facts which are the basis to understand the way of life, thinking, philosophy, common sense and cultural practices that are the core of his authorship.Full text: PDF